2022
DOI: 10.1021/acs.jpcc.2c03129
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemical CO2 Capture Using Substituted Anthraquinones in Homogeneous Solutions: A Joint Experimental and Theoretical Study

Abstract: Electrochemical capture of carbon dioxide (CO 2 ) using organic quinones is a promising and intensively studied alternative to the industrially established scrubbing processes. While recent studies focused only on the influence of substituents having a simple mesomeric or nucleophilicity effect, we have systematically selected six anthraquinone (AQ) derivatives (X-AQ) with amino and hydroxy substituents in order to thoroughly study the influence thereof on the properties of electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 84 publications
(174 reference statements)
1
12
0
Order By: Relevance
“…35,36 In addition, AQ and its derivatives have shown great promise as an electrode material in the electrochemical capture and release of CO 2 . 37,38…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 In addition, AQ and its derivatives have shown great promise as an electrode material in the electrochemical capture and release of CO 2 . 37,38…”
Section: Introductionmentioning
confidence: 99%
“…35,36 In addition, AQ and its derivatives have shown great promise as an electrode material in the electrochemical capture and release of CO 2 . 37,38 Virtual screening approaches based on quantum mechanical (QM) calculation methods provide an alternative and highly promising route to pre-assess potential candidate structures. Considering the numerous possible substitutions of the AQ lead structure (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is caused by intramolecular hydrogen bondings and is absent in the case of alkoxy-substituents, 55 and is already well-described for aprotic solvents in previous experimental and computational studies. 56–58 In contrast to the AQ derivatives, RF did not show remarkable redox features in organic, aprotic solvents, mainly attributed to the low solubility of the highly polar RF structure. As the electrocatalytic O 2 to H 2 O 2 reduction reaction is known to be most efficient for certain material classes in alkaline solutions, 40 homogeneous solutions of the compounds shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies also reported a similar red shift for pristine AQ upon electrochemical reduction. 18,41,42 Duan et al reported that the radical anion exhibits two distinct absorption bands in a shorter range (350−450 nm) and a higher range (550−770 nm), which were assigned to the second and first transitions of the π → π* excited state, respectively. 42 The spectrum showed a reversible behavior of the transition from [BAQMIM] •− to [BAQMIM] after switching the electrode potential to an oxidative potential (0 V vs Ag/Ag + ), and simultaneously the vicinity of the Pt electrode returned to being colorless.…”
Section: mentioning
confidence: 99%